2018
DOI: 10.1007/s00213-017-4820-5
|View full text |Cite|
|
Sign up to set email alerts
|

The hidden therapist: evidence for a central role of music in psychedelic therapy

Abstract: RationaleRecent studies have supported the safety and efficacy of psychedelic therapy for mood disorders and addiction. Music is considered an important component in the treatment model, but little empirical research has been done to examine the magnitude and nature of its therapeutic role.ObjectivesThe present study assessed the influence of music on the acute experience and clinical outcomes of psychedelic therapy.MethodsSemi-structured interviews inquired about the different ways in which music influenced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
164
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(209 citation statements)
references
References 54 publications
(83 reference statements)
9
164
0
12
Order By: Relevance
“…The second session was the focus of the therapeutic process, as only this dose was predicted to induce lasting therapeutic effects. After capsule ingestion, patients laid with their eyes closed while listening to a music playlist . Two therapists adopted a non‐directive, supportive approach, allowing the patient to experience a mostly uninterrupted introspection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second session was the focus of the therapeutic process, as only this dose was predicted to induce lasting therapeutic effects. After capsule ingestion, patients laid with their eyes closed while listening to a music playlist . Two therapists adopted a non‐directive, supportive approach, allowing the patient to experience a mostly uninterrupted introspection.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, psychedelic‐assisted therapy involves only one or two sessions in which a moderate to high dose of a psychedelic compound is given in a supportive environment with the intention of evoking ‘peak’ or ‘mystical‐type’ experiences, characterized by disintegration of ego boundaries and an accompanying sense of connectedness , oneness, or unity . This treatment paradigm differs from the approach of long‐term daily pharmacological intervention associated with conventional antidepressant medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, music and song are the integral part of many indigenous psychedelic traditions (e.g., the icaros sung by shamanic healers during the traditional ayahuasca ceremony; Labate & Pacheco, 2010;Tafur, 2017). In one study of 19 patients undergoing psychedelic therapy with psilocybin for depression, analyses revealed that the music had both "welcome" (desirable) and "unwelcome" (aversive) influences on the patient's experience (Kaelen, Giribaldi, Raine, & Evans, 2018). In many cases, it evoked deeply meaningful, emotional, and therapeutically valuable emotions and imagery.…”
Section: Setting and Musicmentioning
confidence: 99%
“…In many cases, it evoked deeply meaningful, emotional, and therapeutically valuable emotions and imagery. In some cases, however, this was not the case; 6 out of 19 patients referred to "misguidance" and 9 out of 19 spoke to "resistance" as being a part of their experience at some point (Kaelen et al, 2018). However, to date, no empirical research has been conducted to examine the role of music in psychedelic-assisted therapy with people of color.…”
Section: Setting and Musicmentioning
confidence: 99%